Management Production of The Film "Joko Songo" by Bakar Production - Setiawan, Ridho Agus; Rohimi, Primi (Jurnal Ilmiah Syi'ar, 2025)
The national film industry continues to grow, one example being Bakar Production's film, Joko Songo. This film is significant because it highlights local wisdom and the history of Karanganyar heroes while maintaining their authenticity. Studying this film is crucial to understand how effective management strategies can produce quality work even with limited resources.The main objective of this study is to analyze the production management of the film Joko Songo comprehensively, including planning, organization, budget and time management, and identify challenges and implemented solution strategies. This research uses a qualitative approach with a case study design. Data were collected through in-depth interviews with the production team (producer, director, department heads), direct observation on location, and documentation studies (budget plan and production schedule). Data analysis was conducted using thematic techniques to identify patterns and determinants of success. The results show that the film production management is based on the principle of realism rather than blind idealism, where creativity must adapt to the available budget ("maximizing what we have"). Overall, this study concludes that Bakar Production has successfully implemented structured and professional production management with a focus on cost and time efficiency, team cohesion, and creative adaptation to bridge resource limitations in producing high-quality works that are rich in cultural values.